PENGUNAAN SELF REGULATED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB SISTEM PEMBELAJARAN ONLINE DI SMAN 1 MATARAMAN: Rusdiah - Rusdiah, Rurdiah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2021)
This study aims to determine the process and results of using Self Regulated Learning in increasing motivation to learn Arabic in the online learning system during the Covid-19 pandemic at SMA Negeri 1 Mataraman, Banjar, South Kalimantan. The research uses a qualitative approach designed in the form of action research. While the steps used refer to the Mertler model (2011), namely: (1) identification of initial ideas, (2) analysis of general problem finding, (3) general planning of action, (4) developing and implementing action steps (5) evaluating and revise the general design, and (6) develop in the second step of action and so on. The results of the study found that in Cycle I the point of conformity reached 67.7% so that it was certain that students agreed with learning using the concept of Self-regulated learning. However, the acceptance of Arabic lessons is still low, some students still consider Arabic as a difficult subject. While in the second cycle the point of conformity reached 76.5%. Higher than the first cycle after improving the learning pattern in the personal evaluation system section by providing a standard format provided by the teacher. Thus, it can be concluded that students feel enthusiastic in carrying out Arabic learning with an online system if it is done using the concept of self-regulated learning. The theoretical findings in the research are: (1) learning activities that provide wider opportunities for students or are more student centered (student centered learning) provide more opportunities for students to actualize themselves and develop themselves to be better, and (2) student satisfaction in solving their own problems and sharing with friends are important factors in online learning to foster high learning motivation. While the practical findings are (1) it is necessary to make other efforts to make Arabic lessons more interesting for students, even though the average results of the questionnaires are positive but some say they don't like Arabic lessons, and (2) cooperation in problem solving and Freedom in learning is an important thing that must be maintained, because it becomes a dominant factor in the motivation to learn Arabic. Key words: Self-Regulated Learning, motivation, online learning